Mapping of Ancient River Courses by Remote Sensing Techniques and Geophysical Investigation in Northern Arabian Gulf Region - Zainab Adel AL- Muturi * , Sahar Turak .Al-Mulla **, Wala′a Mageed. Al. Mosawi * ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The Northern Arabian Gulf region is important because it have many morphological and landscape, the most important of these landscape are the rivers. So, the present study applied satellite imagery integrating with sub bottom profilers survey to analysis and detect paleoachannel courses for many river and lagoons (Khors) in this region, includes Khor Al-Zubair , Khor Shaitana, Khor Abdulla and Shatt Al-Arab river. Satellite imagery analysis revealed of many traces of discontinued ancient river streams such as Al-Fayeed and Al-Maʼaqel, as well as many ancient courses of presented rivers such as Euphrates, Tigris and Bahamshir. These results were confirmed by sub bottom profilers results which completed in some river channels and that revealed many buried old channels underneath the current river bottoms. Analysis all method depicted that most of these water system sites are exposed to neotectonic indicators affected on the region in general.These morphotectonic activity impacted on the alteration and discontinuity of the river courses in the area under study.From the present study, it seems that the subsidence process is predominant in the region, particularly in the eastern part, and in order to reach a state of equilibrium, this was accompanied by locally uplifting sub-surface structures in Nahr Umr, Al- Zubair, Siba, and Sanam plug sites, as well as the proposed sites between Shatt Al-Arab and Bahamshir rivers.